Heart rates variability difference in different salat positions and five times prayer among male Maahad Tahfiz students / Aznirah Hanum Sekeni - Sekeni, Aznirah Hanum (Faculty of Sport Science and Recreation, 2015)
This study was designed to identifying the effects of the Muslims prayer on the heart rate while performing Sa/at in different positions: standing, bowing, prostrating, and sitting and in five times prayer. 10 subjects (male) participated the study and been choose through random sampling. The aim of this study was to determine the heart rate in different positions and five times prayer among male Maahad Tahfiz students in Pusat Tahfiz Nurul Iman, Perak. The study was analyzed used SPSS version 19.0. This study was used Repeated Measure ANOVA as the statistical analysis. The standing position of the Sa/at produced the highest respectively. It show that there was had significant different of mean in the heart rate of the subject in Maghrib. This study will motivate further study to discover the importants of Salat on human health.